Is routine trauma surgeon presence in the emergency department necessary for all priority one trauma cases? - Nay, Harry Roy (My University, 2014)
Objectives: The majority of injured patients transported to hospital ED’s do not require emergency surgery, yet our protocols require a surgeon to be present on their arrival. There is a drive to develop clinical decision rules so as to apply “secondary triage” criteria to trauma patients in the hope that there can be more efficient use of the surgeons’ time. My objective was to identify the proportion of trauma patients that required emergency trauma surgeon intervention within 60 minutes of patient arrival. Design: A retrospective study of all Priority 1 trauma patients that presented to the ED of three Level 1 trauma centres in three private hospitals in Johannesburg. These units are staffed with ED doctors experienced in trauma management and backed up by either specialist trauma surgeons or surgeons experienced in trauma management. Methods: We analysed data from 4,500 patients in our trauma centre registry (TraumaBank). We identified emergency procedural intervention and emergency operative intervention (within one hour) by a general surgeon. Main Results: Emergency operative intervention occurred in 2.7% of cases and emergency procedural intervention occurred in 0.8% of cases. Existing triage and secondary triage systems performed poorly with unacceptable over and under-triage. Conclusions: Routine surgeon presence during the initial phase of the management of trauma patients is hard to justify. Triage policies need to strike a balance between resources and optimal care. To identify those patients that require emergency operative intervention by trauma surgeons based on pre-arrival triage criteria alone, we need to look primarily at truncal penetrating injury, persistent shock and patients transferred from other facilities.
Keywords: Trauma Centers--manpower